2022
DOI: 10.1002/eat.23784
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver‐reported household food insecurity and child‐reported food insecurity in relation to eating disorder risk factors and symptoms among preadolescent children

Abstract: Objective: To examine the relation of caregiver-reported household food insecurity (FI) and child-reported FI with eating disorder (ED) risk factors and symptoms, including effect modification by gender, in preadolescent children.Method: Data were from the Family Food Study, a cross-sectional study of households with incomes ≤200% of the federal poverty line in southeastern Michigan.Children aged 8-10 years (n = 194) and their female primary caregivers reported separately on FI status. Children reported ED ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Finally, household food insecurity, as reported by the parent/caregiver in the household, may not capture the experience of food insecurity for the adolescent. Studies that have used child-reported food insecurity have found differential associations with children’s health outcomes when compared with parent/caregiver reports ( 49 ) . That being said, there is currently no consistent approach for adolescent reported food insecurity in the USA, which represents an important goal of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, household food insecurity, as reported by the parent/caregiver in the household, may not capture the experience of food insecurity for the adolescent. Studies that have used child-reported food insecurity have found differential associations with children’s health outcomes when compared with parent/caregiver reports ( 49 ) . That being said, there is currently no consistent approach for adolescent reported food insecurity in the USA, which represents an important goal of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Preadolescence (typically defined by researchers as age 8–11 years; Barry et al., 2022; Murray et al., 2022) may be a critical stage for studying the development of EDs. Although EDs are most likely to develop during adolescence (Micali et al., 2013; Stice et al., 2009), there is evidence to suggest these diagnoses are increasing in preadolescence (Nicholls et al., 2011; Petkova et al., 2019; Reas & Rø, 2018).…”
Section: Introductionmentioning
confidence: 99%